Modulation of the pHLIP Transmembrane Helix Insertion Pathway - Karabadzhak, Alexander G. (The Biophysical Society, 2012)
The membrane-associated folding/unfolding of pH (low) insertion peptide (pHLIP) provides an opportunity to study how sequence variations influence the kinetics and pathway of peptide insertion into bilayers. Here, we present the results of steady-state and kinetics investigations of several pHLIP variants with different numbers of charged residues, with attached polar cargoes at the peptide's membrane-inserting end, and with three single-Trp variants placed at the beginning, middle, and end of the transmembrane helix. Each pHLIP variant exhibits a pH-dependent interaction with a lipid bilayer. Although the number of protonatable residues at the inserting end does not affect the ultimate formation of helical structure across a membrane, it correlates with the time for peptide insertion, the number of intermediate states on the folding pathway, and the rates of unfolding and exit. The presence of polar cargoes at the peptide's inserting end leads to the appearance of intermediate states on the insertion pathway. Cargo polarity correlates with a decrease of the insertion rate. We conclude that the existence of intermediate states on the folding and unfolding pathways is not mandatory and, in the simple case of a polypeptide with a noncharged and nonpolar inserting end, the folding and unfolding appears as an all-or-none transition. We propose a model for membrane-associated insertion/folding and exit/unfolding and discuss the importance of these observations for the design of new delivery agents for direct translocation of polar therapeutic and diagnostic cargo molecules across cellular membranes.